2023
DOI: 10.1021/acsomega.3c01110
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of PLpro and Mpro Inhibitors for SARS-CoV-2

Abstract: There are very few small-molecule antivirals for SARS-CoV-2 that are either currently approved (or emergency authorized) in the US or globally, including remdesivir, molnupiravir, and paxlovid. The increasing number of SARS-CoV-2 variants that have appeared since the outbreak began over three years ago raises the need for continual development of updated vaccines and orally available antivirals in order to fully protect or treat the population. The viral main protease (Mpro) and the papain-like protease (PLpro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 85 publications
0
1
0
Order By: Relevance
“…Other studies have shown M pro activity against host proteins involved in immune response, such as galectin-8 [Pablos et al, 2021; Chen et al, 2023]. The proteolytic and immune modulating functions of these enzymes make M pro and PL pro attractive targets for potential antiviral drug intervention [Owen et al, 2021; Cao et al, 2023; Puhl et al, 2023]…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have shown M pro activity against host proteins involved in immune response, such as galectin-8 [Pablos et al, 2021; Chen et al, 2023]. The proteolytic and immune modulating functions of these enzymes make M pro and PL pro attractive targets for potential antiviral drug intervention [Owen et al, 2021; Cao et al, 2023; Puhl et al, 2023]…”
Section: Introductionmentioning
confidence: 99%